A Koli man displaying his catch - Mumbai Archive Project Team (Jio Institute, 2024)
The Kolis fish throughout the year, taking a break only for two months in the monsoon when all fishing activities are halted due to rough seas. The high fishing season starts in August and lasts until October, after which the catch volume declines. By January, it is the low season.